Rok 1956 w osadzie wiejskiej Czerwieńsk w powiecie zielonogórskim = The year 1956 in the rural settlement of Czerwieńsk, Zielona Góra District - Koteluk, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The first signs of the break-up of the Stalinist system in the country appeared in Czerwieńsk in 1956. The inhabitants did not support the collectivisation promoted by the local Communist authorities. One of the things they demanded was the reintroduction of religious education in the primary school. In autumn 1956 after Władysław Gomułka came to power in Poland, the local party and state administration effectively supported the inhabitants? initiatives for the development of crafts and the transformation of the rural settlement of Czerwieńsk into the urban environment.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia